A Bayesian approach to establishing coreference in second language discourse: Evidence from implicit causality and consequentiality verbs. Issue 3 (16th May 2018) - CHENG, WEI; ALMOR, AMIT
Abstract : This study investigated Chinese-speaking English learners' use of implicit causality and consequentiality biases in establishing coreference under a Bayesian view of reference interpretation, which distinguishes between context-based priors about which entity will be re-mentioned and new evidence provided by the referential expression form. In two sentence-completion experiments, participants wrote continuations to sentence fragments with either implicit causality (Experiment 1) or consequentiality (Experiment 2) biases that ended either with or without a pronoun. In both experiments, L2 speakers showed native-like re-mention biases following no-pronoun fragments, indicating native-like predictions about the next-mentioned referent. Following pronoun fragments in NP2-biasing contexts, L2 speakers produced more NP1 continuations than native speakers. We show that this difference lies in different beliefs about pronoun use in the two populations. Specifically, L2 speakers showed a stronger association between pronouns and NP1 referents than native speakers following NP2-biasing verbs.